Triterpene saponins from the roots of Acacia albida Del. (Mimosaceae). (April 2017) - Tchoukoua, Abdou; Tabopda, Turibio Kuiate; Uesugi, Shota; Ohno, Misa; Kimura, Ken-ichi; Kwon, Eunsang; Momma, Hiroyuki; Horo, Ibrahim; Çalişkan, Özgen Alankuş; Shiono, Yoshihito; Ngadjui, Bonaventure Tchaleu
Abstract: Seven previously undescribed bidesmosidic triterpenoid saponins named albidosides A – G, were isolated from a methanol extract of the roots of Acacia albida . Their structures were elucidated using 1D and 2D NMR spectroscopy and mass spectrometry and determined to be bidesmosides of oleanolic acid and of 16α-hydroxyoleanolic acid. Albidosides B – G were assayed for their cytotoxicity against HeLa and HL60 cells using MTT method and microscopic observation. Graphical abstract: Highlights: Seven previously undescribed saponins were isolated from Acacia albida. Their structures were elucidated on the basis of spectroscopic methods. Albidosides A – G were assayed against HeLa and HL-60 cells. Albidosides E and G exhibited moderate cytotoxicities with IC50 13.3–46.7 μM.